NUTRITION ANALYSIS AND CONSUMER ACCEPTANCE OF FLOATING FISH SHAKE CAKE (Decapterus Sp.) - Hasnawati Hasnawati; Harianti Harianti; Husni Angreni; Muh Ayusal Salam (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
Indonesia possesses great potential in the fisheries sector, yet its utilization in functional food products remains limited. Layang fish (Decapterus sp) is a high-quality source of animal protein that has not been optimally used in traditional snacks. This study aims to analyze the nutritional value and consumer acceptability of kue kembang goyang (traditional flower-shaped snack) with the addition of layang fish. The research employed an experimental laboratory method using a Completely Randomized Design (CRD) with three treatments: without layang fish (control), with 20%, and 30% layang fish addition, each tested in three replications. Proximate analysis (moisture, ash, protein, fat, and carbohydrate content) was conducted to determine the nutritional profile, while a hedonic test involving 30 untrained panelists was used to assess color, aroma, taste, and texture. The results are expected to show that the addition of layang fish improves the protein and mineral content without reducing consumer acceptability. This innovation is expected to contribute to the development of nutritious, locally based food products and support the preservation of traditional Indonesian snacks